Tip-Based Nanofabrication Fundamentals and Applications - Tseng, Ampere A. (Springer New York : Imprint: Springer, 2011)
Tip-Based Nanofabrication: Fundamentals and Applications discusses the development of cantilevered nanotips  and how they evolved from scanning probe microscopy and are able to manipulate  environments at nanoscale on substrates generating different nanoscale patterns  and structures. Also covered are the advantages of ultra-high resolution  capability, how to use tip based nanofabrication technology as a tool in the manufacturing of nanoscale structures, single-probe tip technologies, multiple-probe tipmethodology, 3-D modeling and fabrication, and the latest in instrument development. Nanofabrication is critical to the realization of potential benefits in the field of electronics, bioengineering and material science. One enabling  technology in nanofabrication is Tip-Based Nanofabrication, which makes use of  functionalized micro-cantilevers with nanoscale tips. In addition to these areas of coverage, this book also: Discusses the advantages of using tip based  nanofabrication including its ultra-high resolution capability, ease of use, and low instrument cost Demonstrates how to use tip based nanofabrication as a tool in the  manufacturing of nanoscale structure, and for inducing controlled patterns on a  surface with nanometer scale precision Covers the latest in throughput enhancement methodology including using multi-probes, high scanning speeds, and tip-based stamps Presents  recent advances in several tip-induced processes, including thermochemical nanolithography, electric-field-assisted nanolithography, electrochemical nanomachining, nanografting, and dip pen nanolithography Tip-Based Nanofabrication: Fundamentals and Applications is an ideal volume for researchers and engineers working at the forefront of nanotechnology.